Odor and volatile organic compounds biotreatment using compact trickle bed bioreactors (CTBB) in a wastewater treatment plant. (May 2023) - Parzentna-Gabor, Anita; Kasperczyk, Damian; Barbusiński, Krzysztof; Rene, Eldon R.; Urbaniec, Krzysztof
Graphical abstract: Highlights: H2 S, NH3 and VOCs are odorous gases emitted from municipal WWTP. Compact trickle bed bioreactor (CTBB) is highly effective at removing VOCs and odors. A pilot-scale, continuously operated CTBB was tested in a municipal WWTP, Poland. Removal efficiencies: 87.5–98.9 % for H2 S, >99.0 % for NH3, 81.5–99.5 % for VOCs. Abstract: The main aim of this study was to optimize and maximize the impacts of odor and volatile organic compounds (VOCs) biodegradation in a wastewater treatment plant utilizing a pilot-scale compact trickle bed bioreactor (CTBB). A CTBB was built and tested for its long-term performance during which gases were supplied from the tank containing semi-liquid fats, oils, and fat waste. The concentrations of pollutants ranged from 0 to 140.75 mg/m 3 H2 S, 0 to 2500 mg/m 3 VOCs, and 0 to 21.5 mg/m 3 NH3 . The CTBB was tested at different gas flow rates and at two pH values for the liquid phase: pH = 7.0 and 5.0. In the liquid phase, the pollutant removal efficiency was higher at pH = 7.0 than at pH = 5.0. Overall, the removal efficiency was between 81.5 % and 99.5 % for the VOCs and 87.5 % and 98.9 % for H2 S, while NH3 removals were >99 %.